ANALISIS PEMBERIAN TUNJANGAN KINERJA PADA PEGAWAI NEGERI SIPIL KEMENTERIAN AGAMA DI KABUPATEN SAMBAS MENURUT EKONOMI SYARIAH - Hakiki; Munadi; Sri Sunantri (CBJIS: Cross-Border Journal of Islamic Studies, 2022)
The main problems of this research are 1) What is the perception of Civil Servants of the Ministry of Religion in Sambas Regency giving performance allowances? 2) What is the view of Islamic Economics on the provision of performance allowances for Civil Servants of the Ministry of Religion in Sambas Regency? This type of research uses field research that uses qualitative descriptive data, namely research whose data is extracted through observations. The data sources in this study are Civil Servants of the Ministry of Religion in Sambas Regency. Data collection methods used are interviews, documentation, reference tracing. Data collection and management techniques were carried out by conducting in-depth interviews with informants. The results of this study indicate that the provision of performance allowances to Civil Servants of the Ministry of Religion in Sambas Regency mostly experienced an increase in performance and level of discipline which can be seen from two aspects, namely absenteeism and daily performance reports. And most of them are in accordance with the Islamic view, this is because the benefits provided are in accordance with the employee's performance. The implication of this research is that Civil Servants of the Ministry of Religion in Sambas Regency should increase supervision of their employees so that they pay more attention to their duties and responsibilities so that the implementation of the main duties of employees can run well. Therefore, employees should make allowances as motivation to work. This journal is a template for writers. All components needed by a journal such as title, abstract, introduction, and so on have been exemplified here. So just use it by piling it up.